Bilateral transfer phenomenon: A functional magnetic resonance imaging pilot study of healthy subjects - Uggetti, Carla (Neuroradiol J, 2016)
BACKGROUND: The bilateral transfer of a motor skill is a physiological phenomenon: the development of a motor skill with one hand can trigger the development of the same ability of the other hand. OBJECTIVE: The purpose of this study was to verify whether bilateral transfer is associated with a specific brain activation pattern using functional magnetic resonance imaging (fMRI). METHODS: The motor task was implemented as the execution of the Nine Hole Peg Test. Fifteen healthy subjects (10 right-handers and five left-handers) underwent two identical fMRI runs performing the motor task with the non-dominant hand. Between the first and the second run, each subject was intensively trained for five minutes to perform the same motor task with the dominant hand. RESULTS: Comparing the two functional scans across the pool of subjects, a change of the motor activation pattern was observed. In particular, we observed, in the second run, a change in the activation pattern both in the cerebellum and in the cerebral cortex. We found activations in cortical areas involved in somatosensory integration, areas involved in procedural memory. CONCLUSIONS: Our study shows, in a small group of healthy subjects, the modification of the fMRI activation pathway of a motor task performed by the non-dominant hand after intensive exercise performing the same task with the dominant hand.